Effect of harvest index and storage duration on sensory quality of Hass avocado grown in Colombia (2021)
ABSTRACT: Currently Colombia does not have enough studies on avocado sensory quality. So, the aim of this work was to evaluate the harvest index and storage duration on avocado sensory quality. Avocado fruit were harvested from 5 farms in Antioquia. Sensory descriptors were evaluated on a scale from 0 to 5, and general quality (GQ) was evaluated from 0 to 3. Fruit with low GQ exhibit hard, wet, and fibrous textures; they taste green, astringent, spicy, sour, umami, and acid, and the odor is sour, green, and acid. Fruits have a low sensory quality at the beginning of the harvest season. As DM content increases, the sensory quality improves. Orchard location and fruit storage duration influenced its sensory descriptors and general quality.